WEBSITE DESIGN OF BATAK TYPICAL DANCE PACKAGE DALIHAN NATOLU SIGAPITON STUDIO USING WEB ENGINEERING METHODS: Indonesia - Silvianti Silvi; Kiky Rizky Nova Wardani (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
Dalihan Natolu Sigapiton Studio is an art studio located in Sigapiton Village. This studio is one of the efforts to preserve the original village culture with native village teachers to make this dance pure, original that has been passed down from generation to generation. Many want to learn the original Batak dance which is known as the tor-tor dance from Sigapiton Village, however, the long distance makes it difficult for consumers to learn directly from the Dalihan Art Studio Natolu Sigapiton. The current problem is that there is no website or system that can help outsiders to learn traditional village dances. So it can be concluded that there are many wishes from the outside community to learn typical village dances, distance does not prevent them from learning. Based on previous research by Silvianti, Kiky Rizky Nova Wardani [1] entitled “UI Design UX Batak Dance Package at Website-Based Studio Dalihan Natolu Sigapiton Using the Design Thinking Method” has created a website design for Studio Dalihan Natolu Sigapiton. In this study, the aim was to design and build based on previous research by creating a website and adding features to become a Batak Dance Package Website for Dalihan Natolu Siapiton Studio Using the Web Engineering Method, which is a quality software development without spending a lot of money, based on the idea and the needs of the users.